The association between plant and animal protein intake and quality of life in patients undergoing hemodialysis - Darzi, Melika; Rouhani, Mohammad Hossein; Keshavarz, Seyed-Ali (Frontiers in Nutrition, 2023)
Background Hemodialysis (HD) patients often experience a significant reduction in quality of life (QOL). The source of dietary protein intake may influence the renal function and complications of HD patients. The present study assessed the relationship between plant and animal protein intake and QOL in HD patients. Methods 264 adult patients under dialysis for at least three months were included in this cross-sectional study. Dietary intakes were collected using a valid and reliable 168-item semi-quantitative food frequency questionnaire (FFQ) over the past year. Total, animal, and plant proteins were calculated for each patient. To evaluate QOL, Kidney Disease Quality of Life Short Form (KDQOL-SF 1/3) was used. Anthropometric measures were assessed according to standard protocols. Results In this study, the average age of participants was 58.62 ± 15.26 years old; most (73.5%) were men. The mean of total, plant, and animal proteins intake were 66.40 ± 34.29 g/d, 34.60 ± 18.24 g/d, and 31.80 ± 22.21 g/d. Furthermore, the mean score of QOL was 59.29 ± 18.68. After adjustment for potential confounders, a significant positive association was found between total dietary protein intake and QOL (β = 0.12; p = 0.03). Moreover, there was a significant association between plant-based protein intake and QOL (β = 0.26; p < 0.001). However, the association between animal protein intake and QOL was insignificant (β = 0.03; p = 0.60). Conclusion Higher total and plant proteins intake were associated with better QOL in HD patients. Further studies, particularly prospective ones, are needed to corroborate these associations.